Preparação e caracterização físico-química de complexos de inclusão de limoneno em α e β-ciclodextrina - Santos, Polliana Barbosa Pereira dos (2014)
Limonene (LIM) is a monocyclic monoterpene, and one of the main constituents of several essential oils of citric fruits such as orange, tangerine and lemon. Among the essential oils found in citric fruits in general, R-(+)-limonene is the majoritarian component, which can reach concentrations from 90 to 96%. Cyclodextrins (CDs) are cyclic oligosaccharides, most commonly found with six, seven or eight glucose units, known respectively as α-CD, β-CD and γ-CD. They are obtained through the action of the enzyme cyclomaltodextrin glucanotransferase (CGTase) on starch. The CDs are able to form inclusion complexes, altering the physical and chemical properties of the complexed compounds. The objective with this work was to prepare and characterize physical-chemically inclusion complexes of limonene in α-and β-cyclodextrin, studying the properties of the supposed complex formed. Such complex was prepared by means of physical mixture, malaxage and co-evaporation, and was characterized through thermal analysis (differential scanning calorimetry– DSC – and thermogravimetry/derivative thermogravimetry – TG/DTG); gas chromatography coupled to a mass spectrometry -GC/MS; X-ray diffraction – DRX; Fourier infrared transform – FTIR – absorption spectrophotometry; electronic scanning microscopy – ESM;molecular modeling (Docking)and kinetic study of first-phase mass loss. From the results obtained through the analyses, it was possible to point out that both the α-CD and the β-CD formed inclusion complexes with limonene. However, in the DSC curves of the α-CD, which correspond to the methods of MA and CE, it was possible to observe a profile that is different from that observed for pure α-CD and MF. In the DSC curves for β-CD, we observed that the CE presented an endothermic profile that was more significant than were the MF and MA methods. According to the TG/DTGanalyses for α-CD, we can observe that the thermoanalytical profile of the complexes obtained through the MF, MA and CE methods were similar to that of -CD. The TG/DTG curves of limoneneshow mass loss around 100% in the interval of 30-169°C. The TG/DTG curve of α-CD showed two phases of mass loss (between 25 and 120°C) that add up to 10.7% of mass loss followed by decomposition and elimination of carbonaceous material. The TG/DTG curves of β-CD, MF, MA and CE presented a thermoanalytical profile that was similar to the complexes obtained with α-CD. After the evaluation of the mass losses shown on Table 2, we can see figures around 8% for MA and CE in the temperature range between 120 and 270º C, what is an indicator of the higher capacity of limonene complexation. In the results of CG/EM for α-CD, it was possible to observe that MA encapsulated limonene in a ratio of 1:0.49 (limonene: α-CD), but in a ratio that was lower to CE 1:18.11 (limonene: α-CD). Thus, it is shown that CE was the best method, and also that β-CD did not show any complexation in MF and MA. CE showed complexation efficiency of 1:1.44, being considered as the best method for complexation when compared to CE of α-CD. The standard of X-ray diffraction of MF was shown to be quite similar to those found for pure α-CD and β-CD. That is an indicator of low efficiency of complexation. By observing the reflections of MA and CE, we can verify the onset of new peaks and the absence of characteristic peaks of pure α-CD and β-CD. In the analysis of the FTIR spectra corresponding to the inclusion complexes obtained through the methods of MF, MA and CE, it was possible to observe a profile that was quite similar among all the samples. They resemble the spectrum ofpure α-CD and β-CD due to the fact that the complexes have been prepared in a molar ratio of 1:1 (limonene 136.24 g/mol andα-CD 972 g/mol). MEV was performed to evaluate the changes in the crystalline characteristics on the surfaces of pure α-CD and β-CD and after the formation of the inclusion complex, where the results corroborate other findings of the characterization tests. In the molecular modeling (docking), the theoretical results showed more stability in the ligations between α-CD/LIM (-4.49 kcal/mol) than what was observed between β-CD/LIM (-4.04 kcal/mol), once that a lesser expenditure of energy was necessary between α-CD/LIM in relation tothat between β-CD/LIM. The kinetic study of the first phase of decomposition was introduced in this work in order to observe the thermal behavior of the pure α-CD and β-CD, as well as of the complexes obtained in the warming ratios of 2.5-5.0-10 and 15 ºC.min-1, under nitrogen dynamic atmosphere (100 mL. min-1).